Hubungan Tingkat Konsumsi Energi, Protein, Zink dan Zat Besi dengan Status Gizi pada Pasien Kanker Anak yang Menjalani Kemoterapi di Rumah Singgah Denpasar - Rahmasari, Novi Tri; Kusumayanti, G.A Dewi; Mataram, I Komang Agusjaya (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2024)
Cancer is a disease characterized by abnormal cell growth. WHO data for 2018 states that cancer is the second leading cause of death in the world. Child health is a national problem that needs to be given top priority because it really determines the quality of human resources for future generations. The purpose of this study was to determine the relationship between energy, protein, zinc, and iron consumption levels with nutritional status in pediatric cancer patients undergoing chemotherapy at a halfway house in Denpasar, Bali. The type of research was observational with a cross-sectional study design. The sampling technique is non-random sampling/non-probability sampling by means of accidental sampling. 23 sample obtained in the study at a Rumah Singgah Denpasar. This study used univariate and multivariate analysis with the Spearman rank test. The results obtained were that 100% of the samples had an adequate energy consumption level of 100% of the samples had an adequate level of protein consumption and as many as 82.61% of people had an adequate zinc consumption level of and as many as 73.91% of the sample had an adequate iron consumption level. Judging from the normal nutritional status of 69.57% of the sample and 8.70% were obese.Based on Spearman's rank test, the level of consumption of energy, protein, cannot be analyzed for the relationship with nutritional status. There is no relationship between the level of consumption of zinc and nutritional status, and there is a relationship between the level of consumption of iron and nutritional status.